2019
DOI: 10.1016/j.jheap.2019.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Multimessenger tests of Einstein's weak equivalence principle and Lorentz invariance with a high-energy neutrino from a flaring blazar

Abstract: The detection of the high-energy (∼ 290 TeV) neutrino coincident with the flaring blazar TXS 0506+056, the first and only 3σ neutrino-source association to date, provides new, multimessenger tests of the weak equivalence principle (WEP) and Lorentz invariance. Assuming that the flight time difference between the TeV neutrino and gamma-ray photons from the blazar flare is mainly caused by the gravitational potential of the Laniakea supercluster of galaxies, we show that the deviation from the WEP for neutrinos … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 56 publications
2
15
0
Order By: Relevance
“…The first multimessenger test of WEP was between photons and neutrinos with SN 1987A, which showed that neutrinos obey GR to the limits of the measurement (Krauss and Tremaine 1988;Longo 1988). These constraints can be improved using the likely association of IceCube-170922A to the flaring Fermi-LAT blazar (Aartsen et al 2018;Wei et al 2019). Tests have also been performed within photons, GWs, and neutrinos (e.g., Longo 1988;Gao et al 2015;Wei et al 2015Wei et al , 2016Kahya and Desai 2016).…”
Section: The Weak Equivalence Principlementioning
confidence: 99%
“…The first multimessenger test of WEP was between photons and neutrinos with SN 1987A, which showed that neutrinos obey GR to the limits of the measurement (Krauss and Tremaine 1988;Longo 1988). These constraints can be improved using the likely association of IceCube-170922A to the flaring Fermi-LAT blazar (Aartsen et al 2018;Wei et al 2019). Tests have also been performed within photons, GWs, and neutrinos (e.g., Longo 1988;Gao et al 2015;Wei et al 2015Wei et al , 2016Kahya and Desai 2016).…”
Section: The Weak Equivalence Principlementioning
confidence: 99%
“…Some works have used IC-170922A event to constrain the neutrino velocity and the LIV by the timeof-flight delay, e.g., Refs. [16][17][18]. In this work, we will examine the constraints on the superluminal neutrino velocity and the corresponding LIV due to the energy loss of vacuum pair production process for IC-170922A event.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of previous attempts to constrain violations of the WEP via ∆γ ij with GRBs [18,[51][52][53][54], FRBs [6,[55][56][57][58], Supernovae [59,60], Gravitational Waves [61][62][63][64][65][66][67][68][69], Blazar Flares [70][71][72][73][74] or Pulsars [75][76][77][78] have assumed that the gravitational potential is dominated by the contribution from the Milky Way and/or other massive objects such as the Laniakea supercluster. This has two major shortcomings for distant sources: firstly the gravitational potential in Equation 2 should be a fluctuation about the cosmological mean (and thus can take either sign, unlike in the multiple-source approximation where it is strictly additive), and secondly the long range behaviour of the gravitational potential means that we cannot neglect the large-scale distribution of mass [8,9].…”
Section: B Comparison With the Literaturementioning
confidence: 99%